A comparison of estimates of basin-scale soil-moisture evapotranspiration and estimates of riparian groundwater evapotranspiration with implications for water budgets in the Verde Valley, Central Arizona, USA. (January 2016) - Tillman, F.D; Wiele, S.M.; Pool, D.R.
Abstract: Population growth in the Verde Valley in Arizona has led to efforts to better understand water availability in the watershed. Evapotranspiration (ET) is a critical factor in estimating groundwater recharge in the area and a substantial component of the groundwater budget. In this study, two estimates of soil-moisture ET and two estimates of groundwater ET in the Verde Valley are presented and discussed. Basin-scale soil-moisture potential ET (PET) estimates from the soil-water balance (SWB) and basin characteristics model (BCM) groundwater recharge models are compared. Separately, riparian groundwater ET estimated from a method that uses MODIS-EVI remote sensing data and geospatial information, and from the MODFLOW-EVT ET package as part of a regional groundwater-flow model that includes the study area, are also discussed. Somewhat higher PET rates from the SWB recharge model resulted in an average annual ET volume about 17% greater than for PET from the BCM recharge model. For groundwater ET estimates, annual ET volumes were about the same for upper-bound MODIS-EVI ET for perennial reaches of streams as for the MODFLOW ET estimates, with the small differences between the two methods having minimal impact on annual or longer groundwater budgets for the study area. Highlights: Source water for ET can come from groundwater or soil moisture. The source of ET water is important for groundwater budgets. Basin-scale soil-moisture AET is substantially less that PET in the Verde Valley. Groundwater ET estimates are similar for MODFLOW and MODIS methods.